Hematological Ratios versus Disease Characteristics versus Surgeons’ Experience and Expertise: What Stands Out as Predictor of Conversion to Open Cholecystectomy? Hematological and Surgical Factors in Cholecystectomy - Afzal, Maryam; Farooqi, Mehmood Ul Haq; Ashraf, Sobia; Afzal, Muhammad (Pakistan Journal of Health Sciences, 2025)
Conversion of laparoscopic to open cholecystectomy is often a surprise for the surgeon. Objective: To evaluate predictors like inflammatory ratios, gallbladder wall thickness and surgeons’ experience to see what predicts conversion best. Methods: Retrospective cohort study was done on adult patients diagnosed with acute cholecystitis (Tokyo guidelines) at Surayya Azeem Hospital from 2021 to 2024. Data collected included demographics, CBC findings, surgeons’ experience, operation details and ultrasound findings. Patients with chronic cholecystitis, comorbidities and other gallbladder pathologies were excluded. Ratios like NLR, MLR, PLR, SIRI, SII, NLPR and d-NLR were calculated. Chi square, Mann Whittney U, binary logistic regression and ROC analysis were used as per requirement. P-value of less than 0.05 was considered significant. Results: 80% of 475 patients were females. 22 (4.8%) patients underwent conversion. Old age and male gender were associated with adverse outcome. WBC count, NLR, d-NLR, SIRI, SII and NLPR were higher in conversion group. Platelet count, PLR and MLR had no associations. Higher hemoglobin (>12.3 g/dL) and ALC (> 1.8x109/L) were predictive of successful laparoscopic procedure. Highest predictive value for conversion was found for NLR and d-NLR (AUC=0.84) followed SIRI (AUC=0.78) with cut-offs of 4.97, 3.76, and 1.69 respectively. Gallbladder wall thickness of >7mm (AUC=0.64) and inexperienced surgeons (AUC=0.69) also increase the probability of conversion. Conclusion: Systemic inflammatory indices predict conversion better than ultrasound findings and surgeons’ experience. Experienced laparoscopic surgeons should operate on patients with thick gallbladder wall and high inflammatory ratios to minimize the risk of conversion.